Contemporaneous Portal-Arterial Reperfusion during Liver Transplantation: Preliminary Results - G. L. Adani; A. Rossetto; V. Bresadola; D. Lorenzin; U. Baccarani; D. De Anna (Journal of Transplantation)
We prospectively compared sequential portal-arterial revascularization (SPAr, group 1 no. 19) versus contemporaneous portal-hepatic artery revascularization (CPAr, group 2 no. 21) in 40 consecutive liver transplantation (LT). There were no differences in the demographics characteristics, MELD score, indication to LT, and donor's parameters between the two groups. CPAr had longer warm ischemia 66±8 versus 37±7 min (P<.001), while SPAr had longer arterial ischemia 103±42 min (P=.0004). One-year patient's and graft survival were, respectively, 89% and 95% versus 94% and 100% (P=.29). At median followup of 13±6 versus 14±7 months biliary complications were anastomotic stenosis in 15% versus 19% (P=.78), and intrahepatic nonanastomotic biliary strictures in 26% versus none (P=.01), respectively, in SPAr and CPAr. CPAr reduces the incidence of intrahepatic biliary strictures by decreasing the duration of arterial ischemia.